Analysis of methods for determining soil shear strength design values/Grunto stiprumo rodiklių skaičiuojamųjų reikšmių nustatymo metodų analizė - Amšiejus, Jonas (Journal of Civil Engineering and Management, 2000)
Designing foundations by soil safety factors is used for obtaining soil strength design values. The methods [10, 11, 12, 13] used for their calculations and minimal values of investigated coefficients are provided in the standards. The design values of soil characteristics computed by different methods do not match. In reality they should ensure the unique reliability of soil shear strength design values. In the present work, the soil shear strength values are computed by different methods. The experimental data are obtained for sands using direct shear strength apparatus. The comparative analysis of obtained results and methods for predicting the design values of soil strength characteristics is applied. When designing foundations, the relation between soil shear strength and normal stress is treated as linear (1, 2), but the dependency of the lower control limit on normal stress is nonlinear (5). Therefore, methods for getting experimental data of soil shear strength give different results. In corresponding standards, different additional conditions are considered for approximation of the investigated non-linear dependency to the linear one. The soil safety factors used for computing design values of tangent of internal friction angle and cohesion depend on these additional conditions. The approximation of non-linear dependency to the linear one does not allow ensuring the unique probability of soil shear strength design values. It is impossible to ensure the desired unique probability for different values of normal stress using traditional methods and constant soil safety factors. In order to obtain the same probability for soil shear strength values lower than the designed value, the probability-statistical methods should be applied. In this article, the method for determining soil shear strength design values is presented (10, 11). This method ensures the same probability of the soil shear strength design values for any values of normal stress. The probability-statistical methods should be applied for design of foundations when soil strength design values depend on normal stress. In order to apply the investigated methods, the probability of foundation collapse or reliability index β, the mean values of soil strength and their variance should be known. Dimensions of the foundation are obtained from mean value sand variance of soil strength characteristics solving the system of equations (13). The solution of this system is a combination of arguments of foundation design conditions that are investigated as normal random variable. The investigated combination corresponds to the limit state.Article in Lithuanian.First Published Online: 26 Jul 2012